RESISTANCE OF PEPPER (Capsicum annuum L) TO Phytophthora capsici Leon. POWER AND LIMIT (Sciences & Technologie. C, Biotechnologies, 2013)
To realize a varietal selection, the cultivars of pepper (Capsicum annuum L) in Algeria, were inoculated with the local isolates of the fungus Phytophhoracapsici Leon, and used a quantitate test. The measures of the necrosis and died plants were significantly different between cultivars and isolates at the two levels 0.05 and 0.01: the cultivars "Italico II" showed lower sensitivity on all plant organs with means 56.61 mm for the stem,30.27mm for the leaf, and 14.44% died plants; while the cultivar "Esterel" scored higher sensitivity on all organs also with means 122.91 mm for the stem, 49.10mm for the leaf, and 70% died plants, and the other cultivars had agraduate order and were median these two extremes cultivars in sensitivity. Isolate 3 of Jijel area expressed great aggressiveness in all organs of plant. We suggest using the lower cultivars sensitivity especially since it has qualities to the grower and the consumer, or looking forreally resistant variety in different conditions, or try to reducetheinoculumof the fungus by crops rotation.